(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article considers one of the types of formal correlation of emotionally-valued nouns with the meaning of a person when translating an artistic text.The author notes that in the translation there is a categorical shift: the name with the categorical value of the noun in the original text is replaced by a phrase with semantics in the text of the translation.The dominant is indicative. Personal value is replaced by an abstract one and transmits a procedural sign without a face. It is noted that the emergence of this type of formal correlation is due to the absence in Kazakh language of special word names for the females, as well as models, types of education of personal names by qualities, character traits